2012
DOI: 10.1037/a0028587
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing happiness in everyday life: The characteristics and behaviors of online happiness seekers.

Abstract: Although the last decade has witnessed mounting research on the development and evaluation of positive interventions, investigators still know little about the target population of such interventions: happiness seekers. The present research asked three questions about happiness seekers: (1) What are their general characteristics?, (2) What do they purposefully do to become happier?, and (3) How do they make use of self-help resources? In Study 1, we identified two distinct clusters of online happiness seekers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
139
2
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(159 citation statements)
references
References 56 publications
11
139
2
7
Order By: Relevance
“…This suggests, as Parks et al (2012) and others have found, that participants do not necessarily know best when it comes to choosing self-help activities.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This suggests, as Parks et al (2012) and others have found, that participants do not necessarily know best when it comes to choosing self-help activities.…”
Section: Discussionmentioning
confidence: 92%
“…Schueller & Parks, 2012) and smartphone-based (e.g. Parks et al, 2012) selfhelp programs using positive psychology content.…”
Section: Effectivenessmentioning
confidence: 99%
“…That hypothesis was similar to the findings of Heady & Veehoven (as cited in Primasari & Yuniarti, 2010) which capitalized on the influence of happiness to the feeling of satisfaction. What remained constant across different studies is the formulation that happiness is an antecedent, correlate and predictor of positive psychological outcomes (Parks, Della Porta, Pierce, Zilca, & Lyubomirsky, 2012;Lyubomirsky, Diener, & King, 2005). To better understand the dynamics of one's subjective state of well-being, empirical studies were created using quantitative designs (Malkoc, 2011;Toner, Haslam, Robinson & Williams, 2012;Parks, Della Porta, Pierce, Zilca, & Lyubomirsky, 2012;Tkach & Lyubomirsky, 2006;Ganesan & Reyes, 2011) and qualitative designs (Chiu, Hsieh, Yeh, Kuo, Lee, & Yu, 2010;Lu & Gilmour, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated happiness using quantitative research designs (Malkoc, 2011;Toner, Haslam, Robinson & Williams, 2012;Parks, Della Porta, Pierce, Zilca, & Lyubomirsky, 2012;Tkach & Lyubomirsky, 2006;Ganesan & Reyes, 2011). As early as 1960's, happiness was being explored through the use of different survey forms (Argyle as cited in Primasari & Yuniarti, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…En el último ejercicio centrado en el optimismo, se le pide que piense en el mejor escenario futuro que pueda imaginar y que escriba sobre dicho escenario imaginado. Esta aplicación para móviles ha sido sometida a prueba y ha demostrado que mejora el bienestar de los usuarios (Parks, Della Porta, Pierce, Zilca y Lyubomirsky, 2012).…”
Section: Las Tecnologías Positivasunclassified